Epidemiology of bacterial meningitis among children in Brazil, 1997-1998 Epidemiologia de meningites bacterianas entre crianças no Brasil, 1997 a 1998 - Débora PL Weiss; Paul Coplan; Harry Guess (Universidade de São Paulo, 2001)
OBJECTIVE: To document the incidence and the descriptive epidemiology of bacterial meningitis among individuals under age 20 in a geographically defined region in Brazil during the two-year period immediately preceding the introduction of Haemophilus influenzae type b (Hib) vaccines into the national immunization program of Brazil. METHODS: Population-based epidemiological study of all cases of bacterial meningitis reported among residents of Campinas, Brazil, under age 20 (n=316,570) during the period of 1997-98, using comprehensive surveillance records compiled by the Campinas Health Department from cases reported among hospital inpatients, outpatients, emergency room visits, death certificates, and autopsy reports. RESULTS: The incidence of bacterial meningitis (n=274) was 334.9, 115 and 43.5 cases/10(5) person-years (pys) for residents of Campinas under age 1, 5 and 20, respectively. All cases were hospitalized, with an average length of stay of 12 days. Documented prior antibiotic use was 4.0%. The case-fatality rate of bacterial meningitis in individuals under age 20 was 9% (24/274) with 75% of deaths occurring in children under the age of five. The incidence of Hib meningitis (n=26) was 62.8 and 17 cases/10(5) pys in children age <1 and <5, respectively. CONCLUSIONS: The incidence of Hib meningitis in children under the age of 5 in Campinas during 1997-98 was similar to that reported in the US, Western Europe, and Israel prior to widespread Hib vaccine use in those regions. This study provides a baseline for later studies to evaluate changes in the etiology and incidence of bacterial meningitis in children after introduction of routine Hib vaccination in Brazil. OBJETIVO: Documentar a incidência e a epidemiologia descritiva de meningites bacterianas entre pessoas com idade inferior a 20 anos em uma região geográfica definida do Brasil. O período foi de dois anos, imediatamente anterior à introdução da vacina contra Haemophilus influenzae tipo b (Hib), no Programa Nacional de Imunização do Brasil. MÉTODOS: Estudo epidemiológico populacional dos casos de meningites bacterianas notificados entre residentes em Campinas, SP, Brasil, com idade inferior a 20 anos (n=316.570), entre 1997 e 1998. Baseia-se em dados de notificação da vigilância epidemiológica da Secretaria Municipal de Saúde de Campinas, relatados entre casos provenientes de pacientes hospitalizados, atendimento em pronto-socorros, certificados de óbito, autópsias ou atendimentos em ambulatórios. RESULTADOS: A incidência de meningites bacterianas (n=274) foi de 334,9; 115 e 43,5 casos por 10(5) pessoas-ano entre residentes, em Campinas, com idade inferior a 1,5 e 20 anos, respectivamente. Em todos os casos houve hospitalização com uma média de permanência no hospital de 12 dias. O uso prévio de antimicrobianos notificado foi de 4,0%. A taxa de mortalidade total devida a meningites bacterianas entre pessoas com idade inferior a 20 anos foi de 9% (24/274), com 75% das mortes ocorrendo entre crianças com idade inferior a 5 anos. A incidência de meningites causadas por Haemophilus influenzae tipo b (Hib) (n=26) foi de 62,8 e 17 casos por 10(5) pessoas-ano em crianças com idade inferior a 1 e 5 anos, respectivamente. CONCLUSÕES: A incidência e a epidemiologia descritiva de meningites causadas por Haemophilus influenzae tipo b (Hib), entre crianças com idade inferior a 5 anos, em Campinas, SP, Brasil, durante o período de 1997 a 1998, foram semelhantes às relatadas pelos Estados Unidos, Europa Ocidental e Israel no período anterior ao extenso uso da vacina contra o Haemophilus influenzae tipo b nessas regiões. O estudo fornece valores de referência para outras pesquisas posteriores que avaliem mudanças na etiologia e na incidência de meningites bacterianas em crianças, depois da introdução de vacinação rotineira contra Haemophilus influenzae tipo b, no Brasil.